2010
DOI: 10.5688/aj740349
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Elective Diabetes Course on Student Pharmacists' Skills and Attitudes

Abstract: Objective. To assess the impact of an elective diabetes course on student pharmacists' skills and attitudes about diabetes management. Design. A 1-credit elective course on diabetes was developed that included a 1-week simulation experience during which students completed daily insulin injections, glucose checks, carbohydrate counts, and kept a daily log. Assessment. A preintervention and postintervention survey was administered to assess students' attitudes toward and confidence in performing and teaching pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…Only 1 other study has published findings specific to a living with diabetes simulation/role-playing experience; however, this was using a type 1 diabetes regimen. 14 The majority of previous studies involved elective courses that included limited numbers of students, involved multiple exercises, and did not address specifically the ''living with diabetes'' exercise. In contrast to these previous studies reported in the literature, this study involved the assessment of the Living With Diabetes Week simulation alone rather than as part of a larger program.…”
Section: Discussionmentioning
confidence: 99%
“…Only 1 other study has published findings specific to a living with diabetes simulation/role-playing experience; however, this was using a type 1 diabetes regimen. 14 The majority of previous studies involved elective courses that included limited numbers of students, involved multiple exercises, and did not address specifically the ''living with diabetes'' exercise. In contrast to these previous studies reported in the literature, this study involved the assessment of the Living With Diabetes Week simulation alone rather than as part of a larger program.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The incorporation of the DSME classes into the service-learning elective had a significant impact on student confidence in their DSME knowledge and skills. In addition, student performance in organizing and teaching the DSME classes was above average.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] However, there are no published reports of group DSME classes facilitated by pharmacy students. A review of the literature revealed a single study that involved nursing student-facilitated DSME group classes using diabetes conversation maps.…”
mentioning
confidence: 99%
“…In another simulation, pharmacy students engaged in a 6-week patient/provider interaction simulation. While results of diabetes simulations are positive with regards to improving empathy [6,7], self-efficacy [6], confidence in teaching diabetes self-management skills [4,5], and diabetes attitudes [5], none incorporated advanced critical thinking skills related to day-to-day challenges (unexpected hypo-or hyperglycemia, changes in glucose related to illness, stress, or exercise, etc.). Utilizing the expertise of real patients may benefit healthcare providers with regards to attaining complex skills and knowledge [8], improving communication [9], and supporting patient-centered learning [10].…”
Section: Introductionmentioning
confidence: 99%
“…There have been a variety of approaches to simulation to provide education on diabetes management; however, few simulated experiences allow the learner to fully understand the day-to-day challenges of living with diabetes. Pharmacy students have participated in a 1-week simulation experience as if they had diabetes, checking glucose levels, taking saline injections, and logging diet and exercise [4,5]. In another simulation, pharmacy students engaged in a 6-week patient/provider interaction simulation.…”
Section: Introductionmentioning
confidence: 99%